Stretching anatomy. - Nelson, Arnold J., ....-; Kokkonen, Jouko, ....- (Champaign : Human Kinetics, 2007)
See inside every stretch-and maximize flexibility! Stretching Anatomy will arm you with the knowledge to increase range of motion, supplement training, enhance recovery, and maximize efficiency of movement. You'll also gain a detailed understanding of how each stretch affects your body. Stretching Anatomy is like having an X-ray of each stretch, only better. Not only do you see full-color illustrations of the muscles in action, but you also find out how changes in position can alter the muscle emphasis and difficulty and how variations can improve safety and effectiveness. Each exercise includes detailed instruction on how to stretch, when to stretch, primary and secondary muscle emphasis, and which muscles are activated for support. Stretching programs provide three levels of difficulty, including light stretching that can be used as a warm-up or to aid in recovery from soreness or injury. And summary movement tables show how to customize stretching programs to focus on key problem areas. Whether it is increased flexibility or reduced muscle soreness or tension, Stretching Anatomy allows you to see and feel the benefit of proper stretching technique.
Inhoudsopgave : Chapter 1. Neck Chapter 2. Shoulders, Upper Back, and Upper Chest Chapter 3. Arms, Wrists, and Hands Chapter 4. Lower Trunk Chapter 5. Hip Chapter 6. Knees and Thighs Chapter 7. Calves and Feet
Keywords: Sportfysiologie; Stretching